PREVENTIVE HEALTH SEEKING BEHAVIOUR AND KNOWLEDGE RELATING TO HYPERTENSION AMONG NON-TEACHING STAFF OF THE COLLEGE OF MEDICINE, UNIVERSITY OF IBADAN, OYO STATE (2013)
Hypertension contributes largely to morbidity and mortality experienced from cardiovascular diseases worldwide. Studies have been conducted on hypertension among various populations in Nigeria, but only a few have provided data on hypertension-related preventive Health-Seeking Behaviour (HSB) among non-teaching staff in the hospital environment. This study was conducted to determine the preventive HSB and knowledge relating to hypertension among non-teaching staff of the College of Medicine, University of Ibadan (CoMUI). A total of 315 out of 379 consenting non-teaching staff of CoMUI on the University College Hospital premises were involved in this descriptive study. Blood Pressure (BP) was determined as specified in the European Society for Hypertension/World Health Organization guidelines.Body Mass Index was assessed using a known-weight standardized weighing scale and heightometer. Qualitative and quantitative data on knowledge and HSB relating to hypertension were collected using a pre-tested key informant interview guide and a semi-structured questionnaire respectively. Respondents' preventive HSB relating to hypertension were assessed through their responses on preventive practices. Respondents' attitudes towards preventive behaviour and knowledge of hypertension were measured on 20-point scale each. Respondents with scores ?10 points on knowledge and attitude were classified as having good knowledge and positive attitude respectively towards HSB. Data were analysed using thematic approach as well as descriptive statistics, Chi-square and logistic regression. Age range of respondents was 21-60 years with a mean of 42.8±13.3 years; 58.4% were males and 73.7% had tertiary education. Hypertension prevalence among respondents was 25.4% (68.8% male; 31.3% female). Prevalence of overweight and obesity was 33.1% (58.7% male; 41.3% female) and 20.3% (26.6% male; 73.5% female) respectively. Preventive behaviour reported by respondents included non-consumption of alcohol (65.1%), regular BP check-up (46.3%), regular exercise (41.9%) and controlled diets (low salt intake 47.3%, cholesterol-rich fast foods 15.2%). Few respondents (39.3%) had positive attitude towards preventive HSB relating to hypertension. Non-alcohol consumption was 4 times more likely to be observed (OR: 4.2; 95% CI 2.6-6.9) while exercise was twice less likely (OR: 2.1; 95% CI 0.3-0.7) by the respondents. Respondents' educational qualifications and administrative rank were significantly associated with preventive HSB (p<0.05). Majority (77.1%) of the respondents (54.7% male; 45.3% female) had good knowledge of hypertension especially on the symptoms (headache; 69.5%), while 43.8% had low knowledge of hypertension prevention (screening/early detection; 14.9%). All key informants identified too much alcohol consumption, cigarette smoking, non-regular BP check-up (once a month) and poor exercise as major risk factors of hypertension. Many of them did not consider diet as one of the major risk factors of hypertension. Most of the interviewees disclosed that they sometimes indulged in practices which constitute risk factors for hypertension, especially non-regular BP check-up. This was attributed to their busy schedule and unwelcoming attitudes of the physicians when they visited the clinic. Respondents' knowledge of hypertension was good; however many of them had negative attitude to alcohol consumption had, did not exercise regularly and consume cholesterol-rich fast-food. Work-place health promotion and education strategy such as health talk for behaviour change is required to improve the situation.